Highly active and stable P2O5 catalysts supported on mesoporous silica promoted with Ce for the O-methylation of catechol - Hong, Runduo (2024)
P2O5 has been widely used as an acid-base catalyst for the O-methylation of catechol to guaiacol due to its suitable acid strength; however, its stability, which is a significant concern for industrial applications, has not seen significant breakthroughs. Herein, we developed a facile impregnation strategy to synthesize Ce promote P2O5 supported on mesoporous silica (CeP/SBA). The CeP/SBA-500 carbonized at 500 °C exhibited the highest catalytic activity with a catechol conversion of 71.5 %. The high activity stems from the addition of Ce, forming CePO4, which exhibits improved surface acidity compared to P2O5. Importantly, chemisorption and in situ infrared studies revealed that CePO4 shows stronger adsorption of catechol, which then rapidly converts to guaiacol. The CeP/SBA-500 exhibits excellent stability with no activity decrease after 10 h of continuous flow reaction, attributed to the absence of a decrease in CePO4 surface acidity.